Arterial hypertension in women with climacteric syndrome - V. I. Podzolkov; L. G. Mozharova; Yu. V. Khomitskaya (Кардиоваскулярная терапия и профилактика, 2005)
Due to high prevalence of arterial hypertension (AH) in postmenopausal women, this problem has received much attention recently. Hormonal changes in perimenopause cause neuroendocrine disturbances, facilitating AH development and determining some AH features. In peri- and postmenopausal women, AH often combines with climacteric complaints and menopausal metabolic syndrome, that should be taken into account in antihypertensive therapy choice. One of pathogenetically appropriate medication groups is imidazoline receptor agonists.